Patterns of Anti-Inflammatory and Immunomodulating Drug Usage and Microvascular Endothelial Function in Rheumatoid Arthritis - Mangoni, Arduino A.; Woodman, Richard J.; Piga, Matteo; Cauli, Alberto; Fedele, Anna Laura; Gremese, Elisa; Erre, Gian Luca; , The EDRA Study Group; Castagna, Floriana; Piras, Marco; Cadoni, Maria Luisa; Taras, Loredana; et al. (Frontiers in Cardiovascular Medicine, 2021)
Objectives: Specific anti-inflammatory and/or immunomodulating drugs (AIDs) can influence endothelial function which is often impaired in patients with rheumatoid arthritis (RA). We sought to determine whether overall patterns of AID usage are similarly associated with endothelial function. Methods: The reactive hyperaemia index (RHI), a marker of microvascular endothelial function, was measured in 868 RA patients reporting their intake of seven AIDs known to affect endothelial function. Latent class analysis (LCA) was performed to characterise patterns of AID usage. Models for 2–6 classes were compared using the AIC and BIC statistics and Lo-Mendell-Rubin likelihood ratio tests. Associations between the classes and RHI were adjusted for age, gender, body mass index, diabetes, HDL-cholesterol, LDL-cholesterol, family history of ischaemic heart disease, smoking status, RA duration, DAS28 score, steroid dose, existing hypertension, and C-reactive protein. Results: LCA identified five distinct AID usage classes: Class 1, generally low medication usage; Class 2, using either sulfasalazine or non-tumour necrosis factor (TNF) inhibitors; Class 3, methotrexate users; Class 4, TNF-inhibitor users; and Class 5, hydroxychloroquine users. The geometric mean for the RHI for subjects in classes 1 to 5 was 1.92, 1.81, 1.94, 2.10, and 2.07, respectively, with subjects in classes 4 and 5 having better endothelial function than subjects in class 2 (p = 0.003 for each). The glucocorticoid dosage did not influence the classes formed or the association between the classes and the RHI in sensitivity analyses. Conclusion: There were five broad patterns (classes) of AID usage in RA patients. The RHI was relatively lower in users of either sulfasalazine or non-TNF inhibitors. TNF inhibitors or hydroxychloroquine may counteract the negative effects of RA on endothelial function.